2023
DOI: 10.1177/15579883231180982
|View full text |Cite
|
Sign up to set email alerts
|

Men With Both Diabetes and a Family History of Diabetes Were Associated With Depressed Mood in Korean Adults

Abstract: Diabetes mellitus (DM) is strongly associated with depression, especially in women. This study was designed to investigate the gender-specific association between DM and depressive mood by family history of diabetes. Data from the Korea National Health and Nutrition Examination Survey, a population-based cross-sectional survey in 2020, were used. Of 6,133 participants aged 19 years or older, 4,259 participants were included after excluding participants without data of laboratory or physical examination, medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…Participant's positive family history of diabetes was (nondepressed 77.4%, depressed 77.3%), and the p-value (0.991), the difference did not indicate statistical significance, and this is consistent with Kim (28) , which reached a result similar to what this study reached and lagged with Wu (29) who found that a family history of diabetes has an important relationship with depression. Regularity in taking diabetes treatment was studied for the participants in this study, and more than 90% of both depressed and non-depressed groups were regular in taking treatment, and the p-value (0.594), which was not statistically significant and agrees with Lunghi (30) , differs with Mendes (31) .…”
Section: Parameterssupporting
confidence: 60%
“…Participant's positive family history of diabetes was (nondepressed 77.4%, depressed 77.3%), and the p-value (0.991), the difference did not indicate statistical significance, and this is consistent with Kim (28) , which reached a result similar to what this study reached and lagged with Wu (29) who found that a family history of diabetes has an important relationship with depression. Regularity in taking diabetes treatment was studied for the participants in this study, and more than 90% of both depressed and non-depressed groups were regular in taking treatment, and the p-value (0.594), which was not statistically significant and agrees with Lunghi (30) , differs with Mendes (31) .…”
Section: Parameterssupporting
confidence: 60%